ANALISIS DETERMINAN PRODUK KARET OLAHAN INDONESIA KE NEGARA TUJUAN UTAMA PERIODE 2001 - 2023 - Harda, Faticha Putri; Eva Ervani (LPPM - STIE SAKTI ALAM KERINCI, 2025)
Rubber downstreaming has become one of the key strategies to support Indonesia’s economic growth. However, the contribution of processed rubber exports remains relatively low compared to the country’s production capacity. This study aims to analyze the determinants of Indonesia’s processed rubber exports to seven main destination countries during the period 2001–2023. A quantitative approach with panel data analysis using the gravity model was employed. The independent variables examined include the Gross Domestic Product (GDP) of importing countries, economic distance, exchange rate, import tariffs, and labor productivity in the rubber sector, while the dependent variable is the export value of processed rubber products. The results show that the GDP of importing countries and labor productivity have a positive and significant effect on exports, while economic distance has a negative and significant effect. The real exchange rate exhibits a negative but insignificant effect, whereas import tariffs unexpectedly show a positive and significant effect on Indonesia’s processed rubber exports. The coefficient of determination (R²) of 0.6624 indicates that 66.24% of the variation in exports can be explained by the variables included in the model. These findings highlight the importance of enhancing productivity, diversifying products, and optimizing trade policies to strengthen the global competitiveness of Indonesia’s processed rubber industry. Keywords: Exports, Processed Rubber, Gravity Model, Productivity, Import Tariffs